IMPLEMENTASI CRITICAL SUCCESS FACTORS UNTUK MENINGKATKAN KINERJA RS DARMO SURABAYA - Setyowati, Mutiara Puji Lestari Hari; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out and to analyze the implementation of critical success factor as the competitive strategy in the effort of increasing the performance in Rumah Sakit Darmo Surabaya. This research has been done by using qualitative research method with case study approach. Based on the result of the analysis of critical success factors, the strengths, weaknesses, opportunities and threats of Rumah Sakit Darmo Surabaya have been identified by using SWOT analysis. Performance assessment is based on Balanced Scorecard which can be seen from financial perspective, customer perspective, internal business perspective, learning perspective and human resources. Meanwhile, to find out the service quality which has been provided by the company, it is measured by using Public Satisfaction Index (IKM) which is based on the Decree of State Minister for the Empowerment of State Apparatus No. 25/M.PAN/2/2004, in which there are 14 indicators in it. Based on the result of the analysis it can be concluded that by using the Critical Success Factors, strengths, weaknesses, opportunities and threats (SWOT) of the company can be found. Keywords: Critical Success Factors, SWOT Analysis, Performance Measurement.